2013
DOI: 10.1128/aem.03203-12
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Fractionation of 11 Acetogenic Strains Grown on H 2 and CO 2

Abstract: Acetogenic bacteria are able to grow autotrophically on hydrogen and carbon dioxide by using the acetyl coenzyme A (acetyl-CoA) pathway. Acetate is the end product of this reaction. In contrast to the fermentative route of acetate production, which shows almost no fractionation of carbon isotopes, the acetyl-CoA pathway has been reported to exhibit a preference for light carbon. In Acetobacterium woodii the isotope fractionation factor () for 13 C and 12 C has previously been reported to be ‫؍‬ ؊58.6‰. To inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 56 publications
2
30
0
1
Order By: Relevance
“…Furthermore, it has been shown that there is no intramolecular fractionation during acetate formation: the isotope values of the methyl group were similar to the ␦ 13 C values of the overall acetate signal (35). The range of fractionations for different C 1 compounds reported in this study is well within the range reported previously (Ϫ38‰ to Ϫ68‰) for acetogenic cultures grown on H 2 /CO 2 (34,35). And now our data on the conversion of different C 1 compounds to acetate suggest similar discrimination against 13 C irrespective of the individual C 1 compound.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Furthermore, it has been shown that there is no intramolecular fractionation during acetate formation: the isotope values of the methyl group were similar to the ␦ 13 C values of the overall acetate signal (35). The range of fractionations for different C 1 compounds reported in this study is well within the range reported previously (Ϫ38‰ to Ϫ68‰) for acetogenic cultures grown on H 2 /CO 2 (34,35). And now our data on the conversion of different C 1 compounds to acetate suggest similar discrimination against 13 C irrespective of the individual C 1 compound.…”
Section: Discussionsupporting
confidence: 77%
“…The data presented in this report confirmed the overall strong fractionation of acetogens using the acetyl-CoA pathway when H 2 /CO 2 was the substrate (34,35); in addition, it could be shown that the fractionation of cells grown on different C 1 compounds likewise resulted in very strong fractionation and was largely independent of substrate usage (different C 1 compounds). This is in contrast to the findings of several published reports where the rate-limiting step (usually the initial step of a reaction cascade) primarily determined the overall fractionation (20-23, 25, 27, 55, 58).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Assuming an average isotopic fractionation (i.e., e acetate/CO2 ) of -57% (Gelwicks et al, 1989;Heuer et al, 2010;Blaser et al, 2013), we would expect acetogenesis to produce acetate with d 13 C-values around -59% in the mofette soil, where d 13 C CO2 is on average -1.95±0.06% (Bräuer et al, 2004). However, the observed d 13 C of pore-water acetate ranged from -33.6% to -13.9%.…”
Section: Bacterial Groups Assimilating Volcanic Comentioning
confidence: 96%